The ancient Magus' bride. Wizard's blue. Volume 2 - Sanda, Makoto; MacFarlane, Ysabet Reinhardt (Seven Seas Entertainment, 2021)
"In Paris, an orphan boy named Blue is taken under the wing of the magus Gisele in this spin-off manga about the artistry of magic. Not long into his new life, Ao meets a mysterious man named Albert, and is taken by his cheery, laid-back attitude and altruism. But Albert is not what he seems!"--